2022
DOI: 10.1038/s41598-021-04344-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-SARS-CoV-2 antibody levels and kinetics of vaccine response: potential role for unresolved inflammation following recovery from SARS-CoV-2 infection

Abstract: The immune response after SARS-CoV-2 vaccine administration appears to be characterized by high inter-individual variation, even in SARS-CoV-2 positive subjects, who could have experienced different post-infection, unresolved conditions. We monitored anti-SARS-CoV-2 IgG levels and kinetics along with circulating biomarkers in a cohort of 175 healthcare workers during early immunization with COVID-19 mRNA-LNP BNT162b2 vaccine, to identify the associated factors. Subjects with a previous SARS-CoV-2 infection wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…Notably, a similar association has been previously reported by Gianfagna et al. in people undergoing primary BNT162b2 vaccination 5 . Specifically, the authors found that subjects with higher CRP serum levels displayed a faster increase of anti-SARS-CoV-2 IgG levels after receiving two primary doses of BNT162b2.…”
supporting
confidence: 88%
“…Notably, a similar association has been previously reported by Gianfagna et al. in people undergoing primary BNT162b2 vaccination 5 . Specifically, the authors found that subjects with higher CRP serum levels displayed a faster increase of anti-SARS-CoV-2 IgG levels after receiving two primary doses of BNT162b2.…”
supporting
confidence: 88%
“…The results of this study show for the first time that the humoral response developing after receiving a BNT162b2 vaccine booster is significantly associated with pre-booster serum CRP levels. Notably, a similar association has been previously reported by Gianfagna et al in people undergoing primary BNT162b2 vaccination [5].…”
Section: Discussionsupporting
confidence: 88%
“…Multiple reports have consistently shown that the majority of individuals who received a COVID-19 vaccination develop anti-S and anti-RBD IgG in serum by 1 week post-dose 2, irrespective of previous infection status. [70][71][72][73][74] Naaber et al 71 that anti-S and anti-RBD antibody titers correlated well with nAb titers. 72 In a cohort of 137 previously seronegative and vaccinated healthcare professionals, Gianfanga et al 73 found that 100% of these individuals had measurable IgG titers in serum 2 weeks postdose 2, demonstrating that COVID-19 vaccines can elicit a robust and detectable systemic antibody response.…”
Section: Systemic Antibody Response To Covid-19 Vaccinationmentioning
confidence: 95%